KARAKTERISTIK MALOKLUSI GIGI ANTERIOR DENGAN STATUS PSIKOSOSIAL REMAJA AWAL SMPN YOGYAKARTA TAHUN 2013 - Hikma Ridhawati Rahman; Susilarti Susilarti; Dwi Suyatmi (Poltekkes Kemenkes Yogyakarta, 2014)
Malocclusion is the shape of the upper and lower jaw relationshipthat deviates from the standard form which is acceptedas a normal form. The problem that often arises isthe state of the anterior teeth is irregular as the anteriorteeth crowding, gaps anterior teeth, and the protrusion ofthe anterior teeth. Characteristics such as these causemalocclusion sufferers feel self-conscious and uncomfortablewith her appearance, and will directly relate to thepsychosocial status of a person. This reality occurs in susceptibleadolescents especially in adolescents who are ata state of psychosocial transition at age 12-15 years. Typeof malocclusion of the anterior teeth experienced by studentsSMPN Yogyakarta ie anterior teeth crowding, gaps,and protrusion. These three characteristics of malocclusionstudents will be associated with psychosocial status.This study aims to determine the relationship of theanterior teeth malocclusion characteristics with early adolescentpsychosocial status of SMPN Yogyakarta. Type ofresearch is observational. The study subjects came fromstudents of SMPN Yogyakarta as many as 40 people weretaken by random sampling technique were then dividedinto three groups consisting of anterior dental malocclusioncharacteristics of 20 people (50%) with anterior toothcrowding, 11 people (27.5%) the anterior teeth gaps / diastema,and 9 people (12.5%) with protrusion of the anteriorteeth. The results of this study were obtained by questionnairesPIDAQ (Psychosocial Impact of Dental AestheticQuestion) by study subjects and then the data is processedwith SPSS chi-square test (x2) the value of significance (p)= 0.023, which means the value of (p) <0.05 thus Ho rejectedand Ha is accepted.The conclusion can be drawn that there is a statisticallysignificant relationship between the characteristics of malocclusionof the anterior teeth with adolescent psychosocialstatus of SMPN Yogyakarta.